Uso de indicadores para estimar fluxos de matéria seca ileal em eqüinos fistulados - Oliveira, AAMD; Valadares, S. D.; de Queiroz, A. C.; Leao, M. I.; Cecon, P. R.; Pereira, J. C. (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 1998)
This experiment was carried out with six half-bred Bretao-Campolinacolts with ileum fistulated to evaluate the difference in the ileum dry matter flow estimated by chromic oxide, cellulose, NDF, lignin and fecal lignin through the collection of ileum samples digesta at 28 h intervals, totalizing six samples per animal, starting at 10:00 a.m. The animals were fed ad libitum with the following diets: R1: clephantgrass, R2: elephantgrass plus ground corn, and R3: elephantgrass plus ground corn plus soybean meal. The data was statistically described, based on the coefficient of variation. The values of dry matter prececal digestion coefficients were, respectively, for diets 1, 2 and 3, at six schedules, for cellulose (-16.4; 21.4 and 6.6%), NDF(-34.7; 28.8 and -12.8%), to lignin (-51.5; -5.1 and -25.7%), in two schedules for cellulose (-13.4; 25.6 and 21.5%), fecal lignin (-37.1, 16.6 and -6.4%) and chromic oxide (-219.3, 36.4 and 9.5%). The coefficients of variation were, respectively, for the diets i, 2 and 3, at six schedules, for cellulose (148.3; 107.5 and 522.7%), NDF (95.4; 80.9 and 314.3%), lignin (210.2; 752.3 and 209.6%), at two schedules for cellulose(148.5; 80.7 and 70.0%), fecal lignin, (262.4; 177.9 and 723.5%) and chromic oxide (141.1; 158.9 and 473.4%). In diet i, the ileum dry matter now were over estimated for all markers, showing that chosen collection lime to estimate the flows were not adequate. Based on the coefficient of variation of the diets 2 and 3, the cellulose at two schedules was the most marker indicator to determine the ileum dry matter flow.
The use of marker to estimate ileum dry matter flow in fistulated equine
Keywords: equine; flow and dry matter; fistula; markers; ileum